PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. PEDAGANG UNGGUL INDONESIA (X-SELL) - Mohammad Komarudin; Nuridin (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
Analyze the effect of compensation and work discipline on the performance of the employees of PT. Indonesian Superior Trader (X-Sell). The research method uses qualitative and quantitative descriptive analysis, the analysis model used is linear regression both partially or simultaneous. The study population of all employees of PT. Indonesian Superior Traders (X-Sell) totaling 30 employees. The sampling technique of this study uses saturated sampling, which is the technique of determining the sample if all members of the population are used as samples. Result Compensation and work discipline have a positive and significant effect on the performance of employees of IndonesianSuperior Traders (X-Sell) partially or simultaneous.